Analisis Fungsi Manajemen Logistik di Badan Pemberdayaan Masyarakat dan Keluarga Berencana Kota Surabaya - Paramita Boni Lestari; Setya Haksama (Universitas Airlangga, 2017)
Board of Community Empowerment and Family Planning has the main task in a family planning and family welfare program.Logistics management was very importance to support that program. There were 17.020 syringes whichexpired but have not been destroyed in 2016. Author wanted to examine the logistics management function in Bapemas and KB. The variables were logistics planning, budgeting, procurement, receiption, storage, distribution, and elimination.The samples were two warehouse logistics officers.Data collection techniqueswere observation and indepth interview.Requirements planning used the formula of average usage per month multiplied by 3 or 24. The procurement process was done by request to BKKBN Province.Budgeting wasderived from two sources. The sources werestate and local fund. Reception and distribution process was appropriate with technical manual book. Storage facilities reached 94.1% of the BBKBN Centerstandard.While the general provisions saving reached 100%. Eliminating logistics had not done since 2012. The recording process used the forms and books that have been standardized by National BKKBN office.Monitoring started from receipt, storage and distribution. That was done by Province BKKBN office.The conclusion of this research was the Implementation of all functions in accordance with the standards.Keywords: logistics management function, family planning, distribution, procurement